2018
DOI: 10.3389/fpls.2018.01417
|View full text |Cite
|
Sign up to set email alerts
|

Induced Resistance Against Western Flower Thrips by the Pseudomonas syringae-Derived Defense Elicitors in Tomato

Abstract: Western flower thrips (WFT) Frankliniella occidentalis (Pergande) is a key agricultural pest of cultivated tomatoes. Induced host plant resistance by activating jasmonic acid (JA) signaling pathway constitutes a promising method for WFT control. The phytotoxin coronatine (COR), produced by Pseudomonas syringae pv. tomato DC3000 (Pst), mimics the plant hormone JA-Isoleucine and can promote resistance against herbivorous arthropods. Here we determined the effect of Pst and COR on tomato resistance against WFT, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
(95 reference statements)
0
11
1
Order By: Relevance
“…He observed that after removal of trichomes in two wild tomato relatives part of the resistance to two-spotted spider mite ( Tetranychus urticae ) persisted. Recently, reduction of WFT feeding damage was reported in tomato upon infection by Pseudomonas (Chen et al 2018b) and UV-B (Escobar-Bravo et�al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…He observed that after removal of trichomes in two wild tomato relatives part of the resistance to two-spotted spider mite ( Tetranychus urticae ) persisted. Recently, reduction of WFT feeding damage was reported in tomato upon infection by Pseudomonas (Chen et al 2018b) and UV-B (Escobar-Bravo et�al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that exogenous biotic and abiotic elicitors have been used to induce host plant defense against F. occidentalis , for example, Pseudomonas syringae , coronatine [ 10 ], jasmonic acid (JA) [ 3 , 35 ], salicylic acid (SA) [ 36 ], ultraviolet [ 37 ], light intensity [ 38 ], nitrogen fertilizer [ 39 ], CO 2 [ 40 ], secondary substances (α-ionone, eugenol, thymol, carvacrol and alkaloids, etc.) [ 41 , 42 ], and protein inhibitors [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of constitutive or inducible host plant defenses against F. occidentalis may be critical for sustainable thrips control [ 8 , 10 ]. Improving plant resistance by inducing defense mechanisms allows plants to manage energy reserves only when and as needed, and it has been actively studied in many crops [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…to an increase in trichome density, but causes upregulation of metabolites 65 or an increase in plant defense responses 66,67 which is sufficient to increase resistance. However, though several reports indicate that the amount of defensive metabolites produced is a function of the trichome head size [68][69][70] , as we report here, few works have related directly to the connection between trichome head size and pathogen resistance or plant defense pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation or treatment with JA can increase the abundance of trichomes, both glandular and non-glandular, as well as activating plant defensive pathways, leading to increased pest and pathogen resistance 60 64 . In some cases, activation of JA dependent pathways does not lead to an increase in trichome density, but causes upregulation of metabolites 65 or an increase in plant defense responses 66 , 67 which is sufficient to increase resistance. However, though several reports indicate that the amount of defensive metabolites produced is a function of the trichome head size 68 70 , as we report here, few works have related directly to the connection between trichome head size and pathogen resistance or plant defense pathways.…”
Section: Discussionmentioning
confidence: 99%